"You Have to Be Against Bilingualism!" Sociolinguistic Theory and Controversies Over Bilingualism in Catalonia. Issue 4 (1st October 2020) - Woolard, Kathryn A.
Abstract : "Bilingualism" has long been a provocative term in Catalonia, where the concept is more often treated as ideology than as a description of sociolinguistic fact. I present a critical overview of controversies over bilingualism in Catalonia and focus on excavating the rationales underlying Catalanist anti-bilingual stances. This case exemplifies issues in the social contextualization, de-contextualization, and re-contextualization of theoretical concepts that confront critical studies of sociolinguistics and language ideologies more broadly.